The influence of transducer transfer functions and acoustic time delays on the implementation of the LMS algorithm in active noise control systems - Snyder, S.D.; Hansen, C.H. (Journal of sound and vibration, 1990)
Forms of the LMS algorithm have been implemented recently in active noise control systems. Parallel to this, many studies of the convergence properties of the LMS algorithm have been conducted in the field of adaptive signal processing. However, these results cannot be applied directly to active noise control systems as the acoustic time delay and electro/acoustic transfer functions, inherent in an an active noise control system, require modification of the results. In this paper, the effect of the time delay and transfer functions on the convergence properties of the LMS algorithm for a single actuator, single error sensor active noise control system is examined. The results obtained provide some insights into efficient implementation of the algorithm.